Outcomes of Oophorectomy in Pregnancy: A Retrospective Cohort [28N]. (May 2020) - Bouchelion, Ashleigh; Bauer, Alison Marie; Phillis, Maria; Hackney, David; Armstrong, Amy
Abstract : INTRODUCTION: Adnexal masses are common in pregnancy. Our objective is to evaluate outcomes of oophorectomy in pregnant women. METHODS: This is a retrospective cohort study using data from the National Inpatient Sample between 2007 and 2013. Reproductive-aged women undergoing oophorectomy were identified using International Classification of Diseases – 9 diagnosis and procedure codes. Ectopic pregnancies were excluded. The risk of ovarian cancer was compared between pregnant and non-pregnant women undergoing oophorectomy. Secondary outcomes included surgical and pregnancy complications. Univariable analyses and multivariable regression were performed with adjustment for confounding factors. RESULTS: 203, 075 women aged 15–45 years undergoing oophorectomy were identified, of whom 17, 285 (8.5%) were pregnant. Pregnancy was associated with a lower frequency of ovarian cancer diagnosis (0.9% vs 2.5%, P<.001, OR 0.4, 95% CI 0.3 – 0.4). This relationship persisted with multivariable regression (P<.001, aOR 0.3, 95% CI 0.3 – 0.4). Pregnant women were significantly less likely to undergo a laparoscopic procedure or to undergo hysterectomy, omentectomy, or lymph node dissection compared with non-pregnant women. Pregnant women were also significantly more likely to die during hospitalization; this relationship persisted in multivariable regression (0.16% vs 0.05%, P<.001, aOR 4.1, 95% CI 2.5 – 6.6). There were no significant differences in frequency of transfusion or venous thromboembolism. Of pregnant women, 82% delivered during hospitalization for oophorectomy, 78% of these delivered by cesarean. CONCLUSION: Oophorectomy in pregnancy is associated with a lower frequency of ovarian cancer diagnosis, though is associated with higher frequency of laparotomy and death during hospitalization.